New Generation of Fire Hydrants Secure Against Multiple Threats. Issue 4 (1st April 2014) - Spence, Shannon; Kelly, Joseph
Abstract : Coastal towns are always dealing with the corrosive effects of the salty air and water from the ocean on the town's fire hydrants. Because hydrants are predominantly made of metal, are above ground, and exposed to the elements, and their primary function is to deliver water, they are prone to rust and corrosion. This can quickly lead to hydrants being inoperable or in a state of disrepair if an aggressive maintenance program is not regularly exercised. This article discusses a new hydrant to the rescue.